(3fhQ GdTeYI aj HjGf XgQ GdLeYIs - (3Ydj Hf eMeO Hf Ydj, fhQ GdOjf GHf ZGfe GdebOSj,J (B1004 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CeQ GdeUdi HedGReI GdeUdG hHYO abO hQO Ydi SDGd ai GdCQHY GdJi HYO GdLeYI JUdi hjfhi HgG GdeUdi BNQ XgQ s
(3BNQgG (B:s
(3hHdZg eCehdg hGLYdg Chd TGaY hChd eTaY hGMHfG YGdi SfJg hJhafG Ydi edI hChQOfG hGSbfG HcGSI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B195s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(115) s
Keywords: (3GdeLGejYs